2022
DOI: 10.1186/s12872-022-02508-w
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from human placental mesenchymal stem cells ameliorate myocardial infarction via anti-inflammation and restoring gut dysbiosis

Abstract: Background Myocardial infarction (MI) represents a severe cardiovascular disease with limited therapeutic agents. This study was aimed to elucidate the role of the exosomes derived from human placental mesenchymal stem cells (PMSCs-Exos) in MI. Methods PMSCs were isolated and cultured in vitro, with identification by both transmission electron microscopy (TEM) and nanoparticle tracking analysis (NTA). To further investigate the effects of PMSC-Exos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 65 publications
0
20
0
2
Order By: Relevance
“…After 18 h, Firmicutes and the genus Acidaminococcus showed the highest relative abundance. Increases in the genus Acidaminococcus , belonging to the phylum Firmicutes, has been associated with acute myocardial infarction and the flaxseed oil supplementation of lambs’ diet [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…After 18 h, Firmicutes and the genus Acidaminococcus showed the highest relative abundance. Increases in the genus Acidaminococcus , belonging to the phylum Firmicutes, has been associated with acute myocardial infarction and the flaxseed oil supplementation of lambs’ diet [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that exosomes secreted by varieties of immune cells (DCs, macrophages, neutrophils) and non-immune cells (MSCs, platelets) participate in the occurrence and development of chronic inflammation [ 70 , 71 ], and play an important role in regulating the inflammatory microenvironment by regulating gene expression and releasing anti-inflammatory factors ( Fig. 4 ) [ 72 , 73 ]. More importantly, in recent years, exosomes have attracted attention as optimal drug carriers for personalized nanomedicine due to their high biocompatibility, low immunogenicity, and ability to inherit many characteristics of parental cells [74] .…”
Section: Current Progress Of Exosome‐based Delivery Platform To Treat...mentioning
confidence: 99%
“…Death of many cardiomyocytes causes strong inflammation after MI, and studies have shown that intestinal microflora participates in the occurrence of this kind of inflammation ( Wang et al, 2018 ; Zununi Vahed et al, 2018 ). ( Yang et al, 2022 ) pointed out that PMSCs-Exo shows angiogenesis and anti-inflammatory potential in the cell therapy of MI and regulates the intestinal microflora. Gene ontology enrichment analysis of the PMSCs-Exo-lncRNA target gene revealed that lncRNA performs numerous functions at the transcriptional level, suggesting that PMSCs-Exo-lncRNA is a potential target for MI therapy.…”
Section: Ascs-exo-lncrnas With Diverse Organ Sourcesmentioning
confidence: 99%